A low complexity pilot assignment algorithm based on user polar coordinates in CF-mMIMO systems - Shao GUO; Peng PAN; Yaozong FAN (Dianxin kexue)
Absrtact: In order to reduce the pilot contamination in the cell-free massive multi-input multi-output (MIMO) system, a low complexity pilot assignment algorithm based on user polar coordinates was proposed.Firstly, a Gaussian weighted density algorithm was proposed to determine a centroid as the polar coordinates center point in the system coverage area, then pre-assigned the pilot in order according to the angular coordinates, so that users who reused the same pilot had a greater probability of having a longer distance, and henced reduce the pilot contamination.A low complexity distance detection algorithm was then proposed to ensure that the user spacing between any two users multiplexing the same pilot was greater than the threshold.The simulation results show that the proposed pilot assignment algorithm effectively reduce pilot contamination, improve the uplink throughput of 95% users of the system, and achieve a good compromise between performance and complexity.